A Study to Ascertain the Adequacy of Observance of Standard Precautions in Acute Medical and Surgical Wards of a Large Teaching Hospital. (June 2016) - Pandit, Anil; Kulkarni, Meenal
The present study was a cross-sectional analytic epidemiological design to assess the frequency of observance of universal precautions in acute care wards of a large teaching hospital and to assess the epidemiological determinants of such observance. A total population of medical officers, nurses, paramedical and ancillary workers working in acute medical and surgical wards was studied using direct observations recorded on a pre-tested, structured format. The study revealed that hand washing was more frequently practiced by medical officers and ancillary staff (68–93 per cent) as compared to nurses and paramedical staff (38–58 per cent) ( p < 0.01). A significantly higher proportion of medical officers in medical wards (93 per cent) and nurses (63.3 per cent) and ancillary workers in surgical ward (89 per cent) were practicing hand washing ( p < 0.01). The practice of usage of gloves was significantly more frequent among medical officers and ancillary workers (72–100 per cent), while it was quite inadequate among nurses and paramedical staff (28–36 per cent; p < 0.001). However, the use of gloves was significantly better among nurses in the surgical ward and paramedical in the medical ward ( p < 0.05). A linear trend analysis of the use of protective clothing revealed that the odds of nurses adequately using the same were much lower, while those of ancillary workers were much higher as compared to medical officers, the trend being highly significant in both types of wards ( p <0.001). The study reveals a definite need for stepping up educational and motivational methods for observance of universal precautions by health-care workers in large teaching hospitals. In particular, nurses and paramedical workers have been identified as high-risk groups, needing concerted efforts for observing these precautions.